Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1074/jbc.274.17.11848
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Calmodulin-binding Domain of Neuron-specific Protein Kinase C Substrate Protein CAP-22/NAP-22

Abstract: Various proteins in the signal transduction pathways as well as those of viral origin have been shown to be myristoylated. Although the modification is often essential for the proper functioning of the modified protein, the mechanism by which the modification exerts its effects is still largely unknown. Brain-specific protein kinase C substrate, CAP-23/NAP-22, which is involved in the synaptogenesis and neuronal plasticity, binds calmodulin, but the protein lacks any canonical calmodulin-binding domain. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
81
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(84 citation statements)
references
References 43 publications
2
81
1
Order By: Relevance
“…In fact, a recent report describes an NMR structure for a complex between a peptide from Ca 2ϩ pump and CaM which differs from that of the MLCK peptide complex in that it does not assume a collapsed globular structure~Elshorst et al, 1999!. It cannot be assumed that the mC0N9 and Ca 2ϩ pump peptides bind to CaM in the same manner because mC0N9 is unlikely to form a helical structurẽ Takasaki et al, 1999! differently from the Ca 2ϩ pump that takes a helical structure in solution.…”
Section: Structure Of the Ca 2ϩmentioning
confidence: 99%
“…In fact, a recent report describes an NMR structure for a complex between a peptide from Ca 2ϩ pump and CaM which differs from that of the MLCK peptide complex in that it does not assume a collapsed globular structure~Elshorst et al, 1999!. It cannot be assumed that the mC0N9 and Ca 2ϩ pump peptides bind to CaM in the same manner because mC0N9 is unlikely to form a helical structurẽ Takasaki et al, 1999! differently from the Ca 2ϩ pump that takes a helical structure in solution.…”
Section: Structure Of the Ca 2ϩmentioning
confidence: 99%
“…Our observation that DREAM associates with DNA independent of calcium is in contrast to previous work (Osawa et al 2005 (Deisseroth, Heist & Tsien 1998, Zaidi et al 2004. It is also possible that posttranslational modification such as myristoylation/palmytoylation at Cys45/Cys46 could enhance the affinity between CaM and DREAM and decrease the observed EC50, an effect which has been observed in other CaM binding proteins (Takasaki et al 1999). …”
Section: Discussioncontrasting
confidence: 56%
“…However, the involvement of the protein myristoylation in protein-protein interaction has never been clearly demonstrated, although the issue has been the subject of extensive studies (11)(12)(13). Recently, we have shown that the modification is directly involved in the interaction of a brainspecific protein kinase C substrate, CAP-23/NAP-22, with calmodulin (14,15). Furthermore, the phenomena is observed in the binding HIV-1 Nef with calmodulin (16).…”
mentioning
confidence: 92%
“…The peptides were purified by reversed-phase high-performance liquid chromatography (HPLC) using a C18 column (Waters, Bondasphere 5 C18 -300Å, 1.9 ϫ 15 cm). They were judged to be of greater than 95% purity by analytical HPLC and electrospray mass spectrometry (14,25). Peptide concentration was determined by quantitative amino acid analysis.…”
Section: Methodsmentioning
confidence: 99%